An integrative multi-omics approach points to membrane composition as a key factor in E. coli persistence - Silvia J. Cañas-Duarte; Lei Sun; María Isabel Pérez-López; Cornelia Herrfurth; Lina M. Contreras; Ivo Feussner; Chad Leidy; Johan Paulsson; Diego M. Riaño-Pachón; Juan M. Pedraza; Silvia Restrepo (PLoS ONE, 2026)
Many diverse bacteria can enter non- or slow-growing states where they are transiently tolerant to antibiotics. Despite its medical importance, the genetic mechanisms underlying this ‘persistence’ remain largely unknown, especially for spontaneous (type II) persistence that arises during exponential growth. To address this challenge, here we combine genomic, transcriptomic, and lipidomic analysis to explore the persistence mechanisms. We first analyzed the genome of the high-persistence mutant Escherichia coli DS1 ( hipQ ) to identify candidate genes for the high-persistence phenotype. We then compared the gene expression profile of these isolated persisters to that of normally growing cells with RNA-Seq and found that the activation of stress response mechanisms is likely not important in the entrance into hipQ -driven spontaneous persistence during exponential growth. Transcriptomic results also suggest that modifications in the cell membrane are closely linked to persistence, as further corroborated by lipidomic profiles showing a higher level of unsaturated fatty acids in persisters compared to normally growing cells. Taken together, our results indicate that changing membrane composition is associated with persistence, and further our understanding of spontaneous persister cells from the DS1 ( hipQ ) context.